SENTENCING DISPARITY IN TAXATION AND EFFORTS TO OVERCOME THE CONSEQUENCES (Part 2 of 2) - Didit Santoso; Henry Sinaga (Scientium Law Review (SLR), 2022)
The juridical and empirical gaps that occur in many criminal decisions in the field of taxation in Indonesia still cause frequent sentencing disparity problems without a clear justification. It is necessary and urgent to conduct a normative juridical study in answering 2 (two) formulations of existing problems, considering that the primary function of taxes is the budgetary function and the function of regulating (regulerend). It is concluded that currently, there is only Article 44B of the KUP Law that can reduce sentencing disparity in the field of taxation in Indonesia, so the concept of equality before the law and checks and balances are needed in handling sentencing disparity in Indonesia, which generally consists of disparity across the integrated criminal justice system, horizontal judicial disparity, and vertical judicial disparity. It is suggested that there should be a Supreme Court Regulation on Guidelines for Sentencing of Taxation Crimes and a Supreme Prosecutor's Regulation on Guidelines for Prosecution and Pre-Prosecution of Criminal Acts in the Field of Taxation, examination, and public dissemination of every decision that results in a decision containing sentencing disparity without a clear justification, and strengthening the supervisory institutions of each integrated criminal justice system, such as the Judicial Commission, and the Supreme Court.